ASSESSING THE RELIABILITY AND VALIDITY OF QUALITATIVE INTERVIEWS: A PILOT STUDY ON INTERNATIONAL STUDENTS’ EXPERIENCES IN A SMALL LIBERAL ART COLLEGE IN THE USA - Inan, Seyma (International Journal of Research Science and Management, 2024)
This qualitative paper explores the use of qualitative interviews within social science research, emphasizing the critical need for data validity and reliability, challenges that are particularly pronounced for researchers new to conducting structured interviews. Conducting a pilot test is a critical step in refining the qualitative data collection process, offering researchers an opportunity to enhance the actual interview based on preliminary findings. This paper outlines the methodology employed in a pilot study aimed at verifying the validity of qualitative data concerning the experiences of international students in a small liberal art college in the USA. Additionally, the paper highlights the significance of pilot testing the interview framework. A semi-structured interview format was chosen for the pilot, conducted with undergraduate students. The outcomes from this pilot test indicate that the chosen interview instrument is effective in capturing the nuanced aspects of the students' experiences.